Zygotic amplification of secondary piRNAs during silkworm embryogenesis - Kawaoka, Shinpei (Cold Spring Harbor Laboratory Press, 2011)
PIWI-interacting RNAs (piRNAs) are 23–30-nucleotide-long small RNAs that act as sequence-specific silencers of transposable elements in animal gonads. In flies, genetics and deep sequencing data have led to a hypothesis for piRNA biogenesis called the ping-pong cycle, where antisense primary piRNAs initiate an amplification loop to generate sense secondary piRNAs. However, to date, the process of the ping-pong cycle has never been monitored at work. Here, by large-scale profiling of piRNAs from silkworm ovary and embryos of different developmental stages, we demonstrate that maternally inherited antisense-biased piRNAs trigger acute amplification of secondary sense piRNA production in zygotes, at a time coinciding with zygotic transcription of sense transposon mRNAs. These results provide on-site evidence for the ping-pong cycle.